Analysis of Fluoride Content in coffee Available in Nagercoil Market of Kanyakumari District (Tamil Nadu) - Umayorubhagan, V.; Prema Mary, F.; Selvaraj, V.; Sri Renganathan, P. (Asian Journal of Chemistry, 2010)
Fluoride is a diseases caused by the excessive ingestion of fluoride. Intake of coffee is a routine affair every day for most of the population and some people have it as a diet, not as a beverage. This shows the necessity and urgency to carry out the investigation. This work involves the determination of fluoride level in whole range of the locally available coffee powder.